Breaking chains across generations: exploring the nexus between intergenerational educational mobility and domestic violence among Indian women - Choudhary, Akanksha; Singh, Ashish (Frontiers in Human Dynamics, 2024)
Introduction: In this article, authors have investigated the relationship between intergenerational educational mobility and the chances of experiencing domestic violence among Indian women. This perhaps is the first ever attempt to demonstrate this relationship not just in the Indian context but also in the global scholarship on domestic violence. Methods: The analysis is based on logistic regression using the data ‘India Youth Survey: Situation and Needs’. Authors have controlled for various individual, familial, and community-level factors in achieving the results. Results: Findings indicate that women who have more years of education than their mothers have significantly lesser chances of experiencing domestic violence. Furthermore, daughters whose mothers have been victims of domestic violence are highly likely to experience it themselves. Besides, women whose husbands consume alcohol, come from low income strata or live in nuclear families have significantly higher odds of experiencing domestic violence. Also, it was observed that the odds of experiencing domestic violence vary significantly for different castes, regions, religions as well as rural and urban areas. Insights from this study can contribute to policymaking aimed at empowering women through education, especially when their mothers haven't had a significant education. Additionally, the study further substantiates the role of factors such as maternal experience of domestic violence, husband's alcohol consumption, low income levels, and family structure in determining the likelihood of experiencing domestic violence. Therefore, the findings support existing scholarship for designing targeted interventions to address these specific risk factors, ultimately contributing to creating safer environments for women. Conclusion: Merely educational attainments do not affect the chances of domestic violence to a large extent. It is probably the confidence a woman derives on account of better educational attainments as compared to her previous generation that influences her take on the menace of domestic violence.